Den færøske modersmålsordbog - en midtvejsrapport - Johansen, Anfinnur; Jacobs, Jógvan í Lon (Nordiske Studier i Leksikografi, 1995)
This article is a half-way report from the Faroese monolingual dictionary, which is being prepared. It gives an outline of the edition of the dictionary which will be published in a year or two. The first part contains an outline of Faroese dictionaries historically and Faroese book publications during the last 173 years. The second part deals with the problems conceming the editing of the dictionary, especially the selection of the head words and, in this context, the conflict between purism and the spoken language. The general problems conceming the situation of Faroese as an intermediate form of language between West Scandinavian and Bast Scandinavian areas are discussed: where is Faroese placed typologically in this spectrum? What do we do with all the Danish loanwords and the neologisms?